Influence of Doping of Titanium Dioxide by Zirconium and Niobium on its Morphology - L.M. Humeniuk; I.M. Budzulyak; R.V. Ilnytskyy (Журнал нано- та електронної фізики)
Structure porosity and specific surface area of undoped and doped nanodispersed titanium dioxide with Zr, Nb was investigated. The porous structure of TiO2 is caused by its intervals between nanoparticles and their agglomerates. Surface morphology of obtained materials was determined by isotherms of nitrogen adsorption-desorption. Specific surface area of nanodispersed titanium dioxide, according to the results, consists 182 m2/g. It was found, that during doping of titanium dioxide with zirconium comparing to origin TiO2 specific surface increases in 30 %, and for niobium-doped decreases in 20 %. Pore-size distribution for TiO2 correspond to the value of 10-15 nm.